2006
DOI: 10.1007/s11547-006-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary nodules in osteosarcoma patients: differential diagnosis of central venous catheter–related infections in the lungs

Abstract: Placement of a central venous catheter for infusion therapy, chemotherapy and blood sampling has improved the quality of life of cancer patients. The most common complications of the use of central venous catheters include infection and venous thrombosis whereas pulmonary septic emboli are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the multivariate analysis, only bone surgery was a risk factor for the occurrence bacterial complications 24. Longhi et al25 found that among patients with OSA, infection of the central catheter with fever were found in 5.6% of them. Authors suggest that the most common complications of the use of central venous catheters were infection and venous thrombosis whereas pulmonary septic emboli were rare 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the multivariate analysis, only bone surgery was a risk factor for the occurrence bacterial complications 24. Longhi et al25 found that among patients with OSA, infection of the central catheter with fever were found in 5.6% of them. Authors suggest that the most common complications of the use of central venous catheters were infection and venous thrombosis whereas pulmonary septic emboli were rare 25.…”
Section: Discussionmentioning
confidence: 99%
“…Longhi et al25 found that among patients with OSA, infection of the central catheter with fever were found in 5.6% of them. Authors suggest that the most common complications of the use of central venous catheters were infection and venous thrombosis whereas pulmonary septic emboli were rare 25. We observed that only 6% of infections were associated with post-operative wound infection after surgical procedure, while BSI and the UTI were the most frequent type of infection complication.…”
Section: Discussionmentioning
confidence: 99%